2017
DOI: 10.1371/journal.pone.0172022
|View full text |Cite
|
Sign up to set email alerts
|

Perception-production relations in later development of American English rhotics

Abstract: It is known that some adult listeners have more sharply defined perceptual categories than others, and listeners with more precise auditory targets are also more precise in their production of contrasts. There is additionally evidence that children who have not yet mastered production of a contrast show diminished performance on perceptual measures of the same contrast. To date, however, few studies have investigated developmental perception-production relations using the fine-grained measures typical of adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 57 publications
3
17
0
Order By: Relevance
“…Previous perception studies usually involved young infants focusing on their abilities to discriminate some simple sound contrasts, whereas production studies necessarily involved older children with better articulatory control. Recently, there are some studies investigating the link between perception and production in children's acquisition of consonants, notably English /r/ (e.g., Idemaru & Holt, 2013;McAllister Byun & Tiede, 2017), but mixed results were presented. Very little data have been reported on the link between children's tone production and perception.…”
Section: The Acquisition Of Cantonese Tonesmentioning
confidence: 99%
“…Previous perception studies usually involved young infants focusing on their abilities to discriminate some simple sound contrasts, whereas production studies necessarily involved older children with better articulatory control. Recently, there are some studies investigating the link between perception and production in children's acquisition of consonants, notably English /r/ (e.g., Idemaru & Holt, 2013;McAllister Byun & Tiede, 2017), but mixed results were presented. Very little data have been reported on the link between children's tone production and perception.…”
Section: The Acquisition Of Cantonese Tonesmentioning
confidence: 99%
“…Specifically, greater acuity was associated with a larger contrast in the sounds produced. This link between perception and production has been demonstrated in vowels (Fox, 1982;Franken et al, 2017;Perkell et al, 2004), sibilants (Ghosh et al, 2010), and rhotic consonants (McAllister Byun & Tiede, 2017). Similarly, significant correlations were observed between acoustic measures of listeners' perceptual prototypes for phonemes and acoustic measures of their own productions of the phonemes; this relation was observed in voice onset time for stop consonants and frequencies of spectral peaks for voiceless fricatives (Newman, 2003).…”
mentioning
confidence: 60%
“…he link between speech perception and production has been investigated in previous studies (Fox, 1982;Franken, Acheson, McQueen, Eisner, & Hagoort, 2017;Ghosh et al, 2010;McAllister Byun & Tiede, 2017;Newman, 2003;Perkell et al, 2004), which have found that individuals' perceptual abilities to distinguish between similar-sounding phonemes were correlated across speakers with the amount of contrast between those phonemes that individuals produced in their own speech. Specifically, greater acuity was associated with a larger contrast in the sounds produced.…”
mentioning
confidence: 99%
“…Since the F2 height contributes as a secondary cue in the perception of rhoticity (Idemaru & Holt, 2013), F3-F2 distance may be a more robust indicator of perceptual accuracy than F3 alone (Flipsen, Shriberg, Weismer, Karlsson, & McSweeny, 2001; McAllister Byun & Tiede, 2017). Furthermore, z-scores of F3-F2 and F3/F2 have been shown to control for age/sex differences across individuals (Flipsen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen TD children were recruited from a sample of recent participants in a similar study (McAllister Byun & Tiede, 2017). In both the original and current studies, inclusionary criteria included parent report of no major neurobehavioural, speech-language, or hearing impairment and passing a hearing screening at 500, 1000, 2000, and 4000 Hz at 20 dB HL.…”
Section: Methodsmentioning
confidence: 99%